Cho hàm số \(f(x)=x^3-x^2+2x-1\). Gọi \(F(x)\) là một nguyên hàm của \(f(x)\). Biết rằng \(F(1)=4\). Tìm \(F(x)\).
\(F(x)=\dfrac{x^4}{4}-\dfrac{x^3}{3}+x^2-x\) | |
\(F(x)=\dfrac{x^4}{4}-\dfrac{x^3}{3}+x^2-x+1\) | |
\(F(x)=\dfrac{x^4}{4}-\dfrac{x^3}{3}+x^2-x+2\) | |
\(F(x)=\dfrac{x^4}{4}-\dfrac{x^3}{3}+x^2-x+\dfrac{49}{12}\) |
Chọn phương án D.
\(\begin{aligned}F(x)&=\displaystyle\int f(x)\mathrm{\,d}x=\int\left(x^3-x^2+2x-1\right)\mathrm{\,d}x\\
&=\dfrac{x^4}{4}-\dfrac{x^3}{3}+x^2-x+C.\end{aligned}\)
\(\begin{aligned}\text{Mà }F(1)=4\Leftrightarrow&\,\dfrac{1^4}{4}-\dfrac{1^3}{3}+1^2-1+C=4\\
\Leftrightarrow&\,C=\dfrac{49}{12}\end{aligned}\)
Vậy, \(F(x)=\dfrac{x^4}{4}-\dfrac{x^3}{3}+x^2-x+\dfrac{49}{12}\).